Identification of organizational barriers to HPV vaccination uptake in medical students in southern Italy: a cross-sectional study - Sorrentino, Michele; Mercogliano, Michelangelo; Esposito, Federica; Lamberti, Agostina Maria; Buonocore, Gaetano; Riganti, Carla; Triassi, Maria; Palladino, Raffaele (Frontiers in Public Health, 2023)
Despite proven efficacy, HPV vaccination coverage is still suboptimal. Factors influencing vaccination uptake are education attainment, socio-economic position, and knowledge about HPV. This study aimed to assess HPV vaccination uptake and its correlates among medical students and identify logistic-organizational barriers, knowledge, and attitude towards HPV vaccination to improve current public health vaccination strategies. Medical students, with their acquired biological knowledge, were selected as low-risk groups for HPV vaccination uptake. This cross-sectional study was conducted using a validated questionnaire. The first three years students were preferentially invited. Eventually, the invitation was extended to every medical student. Logistic multivariable regression was used to assess determinants of HPV vaccination uptake. Additional analysis explored determinants of knowledge and attitude toward HPV vaccination. Finally, a sensitive analysis was conducted to further assess the effect of knowledge and attitude on HPV vaccination rate. A total of 882 medical students participated, with 74,5% enrolled in the first three years. HPV vaccination uptake was 55.5%, ranging from 78.5% for females to 16.5% for males. Male sex and increasing age were consistently associated with a lower vaccination uptake (male sex: OR 0.03, CI 0.02-0.05; age: OR 0.77, CI 0.68-0.88), whilst progress in their academic career was associated to higher likelihood of being vaccinated (6th year: OR 3.45, CI 1.24-9.57). These associations were confirmed when considering knowledge and attitude towards HPV. Also, an active outreach from healthcare institutions was associated with higher likelihood of receiving HPV vaccination (OR 1.70, CI 1.09-2.65). HPV vaccination in medical students was higher than general population, however, still suboptimal. An active and up-to-date call strategy and extending the free-of-charge offer are essential measures to improve vaccination uptake. Findings support the need to improve public health strategies and increase awareness and knowledge regarding HPV vaccination.